Seismic Microzonation of Toba Lake Region Using Microtremor Analysis - Surya Nanda, Fauzan; Raharjo, Furqon; Ahadi, Suaidi (Journal of the Physical Society of Indonesia, 2026)
The Toba Lake region, characterized by complex volcanic and tectonic history, represents a significant seismic hazard zone due to its proximity to the active Sumatra Fault System and heterogeneous geological conditions. This study applies the Horizontal to Vertical Spectral Ratio (HVSR) method using microtremor data to assess seismic vulnerability across the region. Three-component microtremor recordings from 29 stations were analyzed to derive key seismic parameters including predominant frequency (), amplification factor (), dominant period (), and seismic vulnerability index (). The results reveal significant spatial variations in seismic hazard parameters, with high vulnerability zones concentrated in the central and southern areas, characterized by low predominant frequencies (0.6-1.2 Hz), high amplification factors (up to 12.0), long dominant periods (1.2-2.1 seconds), and elevated vulnerability indices (Kg > 8.0). These zones correspond to Quaternary alluvial deposits with soft, unconsolidated sediments. Conversely, northern and northwestern regions exhibit lower vulnerability with high predominant frequencies (>2.0 Hz), low amplification factors (<4.0), short dominant periods (<0.6 seconds), and reduced vulnerability indices (Kg < 3.0), correlating with consolidated Miocene volcanic rocks. Critical high-risk areas include measurement points LT34, LT14, LT17, LT21, and LT49, while point LT20 in Tarutung, located along the Sumatra Fault Zone, demonstrates the compound effect of active tectonics and soft geological conditions. The resulting microzonation maps provide a regional-scale framework for seismic hazard identification and disaster risk mitigation planning, and can serve as a reference for prioritizing areas requiring more detailed, site-specific investigations.